Returning an employee to work on the basis of a court judgment - Antić Aleksandar; Ćorac Sanda (Zbornik Radova Pravnog Fakulteta u Nišu)
In case of unlawful termination of employment, the employee may request from the court during the court proceedings to oblige the employer to return him/her to work. However, reinstatement of the employee is not mandatory. In case of unlawful termination of employment, the reintegration of an employee into the work process entails numerous legal and practical problems. Neither the Labor Act nor other laws envisage specific provisions on the employers' conduct if it is impossible to carry out the return to work due to the occurrence of certain objective circumstances, nor do they provided for the possibility for the employee who has been returned to work to replace this right with monetary compensation within a certain period, in case he did not adapt to the changed work environment after returning to work or was employed by another employer immediately before the judgment was passed. The legislator has made a distinction between unlawful termination of the employment due to the lack of a legal ground and unlawful termination of employment due to non-compliance with the termination procedure stipulated in the employment contract. Under the former legal provisions which had been in force before 2014 (when the Labor Act was substantially amended) and the unanimous position of judicial practice, the violation of provisions on notification or Statute of limitations on giving a notice of dismissal, or any other termination procedure, always leads to the conclusion on the unlawfulness of dismissal and results in annulment of the decision. Under the currently applicable legal solution, the position of the weaker party in the employment relationship is significantly aggravated because the employee does not have to be returned to work if the employer has made a mistake in the dismissal/termination procedure. In order to analyze the problems related to the return to work of an employee based on a court judgment and consider related theoretical and practical issues, the paper is divided into two parts. The first part of the paper analyzes the provisions of the Labor Act on the legal consequences of unlawful termination of employment. The second part discusses the essential features of the provisions of the Enforcement and Security Act which regulate enforcement procedure for returning the employee to work.